PARTISIPASI ORANG TUA DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PKn DI KELAS VII1 SMP NEGERI 2 TIGO NAGARI KABUPATEN PASAMAN - Nila Sari; Syafreni Tama Putri; Khairul Anwar (STKIP Pesisir Selatan, 2022)
Lack of interest in children's learning in PKn subjects in Class VII1 State Junior High School 2 Tigo Nagari Pasaman Regency, with the aim to find out the participation of parents in increasing students' learning interest in PKn. subjects in Class VII1 Of State Junior High School 2 Tigo Nagari Pasaman Regency. This type of research is qualitative research. Using descriptive methods. Informants are determined by purposive sampling. with data collection techniques through observation, interviews and documentation studies. Based on the results of research conducted showed that parents have provided participation in increasing students' learning interest in PKn subjects. It is seen that parents always pay attention to student lessons at home, advise students at home, parents always try to increase students' learning interest. Various participations made by parents to students at home in increasing their learning interest, especially in PKn subjects, namely: (1) Providing motivation, (2) Completing Books, (3) Encouraging, (4) Telling to learn, (5) Giving punishment, (6) Giving advice, (7) Giving rewards.